MENGELOLA RISIKO KEUANGAN : PENTINGNYA DIVERSIFIKASI PORTOFOLIO DAN KOMUNIKASI DI TAHUN 2025 - Ni Luh Putu Suarmi Sri Patni; I Wayan Susrama; Fransisca Wuri Wulandari; Windy Permata Suyono; Kunto Ajibroto; Andi Zulfikar Darussalam (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to analyze the importance of portfolio diversification and effective communication in managing financial risk in 2025. Changes in global economic conditions that are increasingly dynamic and complex require innovative and adaptive risk management strategies. Portfolio diversification is one of the main approaches to minimize losses and increase investment stability. In addition, transparent and accurate communication between market participants, investors, and financial managers plays an important role in making the right decisions. This research uses the literature study method and secondary data analysis to evaluate diversification and communication practices in the modern financial context. The results show that a combination of optimal portfolio diversification and effective communication can improve financial resilience amid global economic challenges. The findings provide important insights for investors, money managers, and policymakers in crafting more resilient financial strategies in the coming era. The result shows that the involvement of networks in social media affects the effectiveness of Fight the Haze campaign. Also, the social relations between organizations that are united under the alliance of Fight the Haze campaign are based on sentimental networks.